2011
DOI: 10.4269/ajtmh.2011.11-0171
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Use of Oral Rehydration Salts and Other Oral Rehydration Therapy for Childhood Diarrhea in Kenya

Abstract: Reductions in the use of oral rehydration therapy (ORT) in sub-Saharan Africa highlight the need to examine caregiver perceptions of ORT during diarrheal episodes. Qualitative research involving group discussions with childcare providers and in-depth interviews with 45 caregivers of children < 5 years of age who had experienced diarrhea was conducted in one rural and urban site in Kenya during July–December 2007. Diarrhea was considered a dangerous condition that can kill young children. Caregivers preferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 19 publications
2
30
1
Order By: Relevance
“…This is not in agreement with a study conducted in Guniea-Bissau [14]. Other study indicated that many caregivers are waiting the advice of the health workers to ensure that ORS is the suitable treatment [29]. This misunderstanding might be the reason for the lack of association between the presence of ORS at home and ORT use.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…This is not in agreement with a study conducted in Guniea-Bissau [14]. Other study indicated that many caregivers are waiting the advice of the health workers to ensure that ORS is the suitable treatment [29]. This misunderstanding might be the reason for the lack of association between the presence of ORS at home and ORT use.…”
Section: Discussioncontrasting
confidence: 63%
“…In our study, health workers were information sources for the majority of the caregivers. In a qualitative study conducted in Kenya, many of the caregivers needed advice from the health workers to provide ORT to their children [29]. This is not in line with the WHO recommendation that fluids should be given immediately at the onset of diarrhea [23].…”
Section: Discussionmentioning
confidence: 99%
“…Household diarrhoea endemicity variable was included to examine if the magnitude of diarrhoea in the households has any bearing on care-seeking behaviour. Residents from high endemic households were less likely to visit health facilities but were more likely to use ORS previously obtained from HSAs or a health facility [24]. Frequent diarrhoea occurrences may compel households to stock ORS from healthy facilities, which may later be used to treat diarrhoea cases at home.…”
Section: Discussionmentioning
confidence: 99%
“…The low utilization of public health facilities is alarming and this might reflect the mistrust of the communities in public health facilities dues to various reasons such as absenteeism, behavior and lack of medicines [28]. The private health care providers have been consulted for the health care seeking both in intervention and control settings.…”
Section: Discussionmentioning
confidence: 99%